Hydrogen transfer through different crystal phases of nickel oxy/hydroxide. Issue 39 (23rd August 2018) - Elbaz, Yuval; Furman, David; Caspary Toroker, Maytal
Abstract : Hydrogen transfer is modeled for nickel hydroxide phases at several pathways and mechanisms. Abstract : Nickel hydroxide phases are common in several energy conversion devices including battery electrochemical cell electrodes. These materials have a unique layered structure that may facilitate hydrogen transfer between oxygen sites and allow using this material also for proton conducting fuel cells. In order to assess this functionality, we use Density Functional Theory+U together with the Nudged Elastic Band method to calculate minimum energy diffusion paths and hydrogen vacancy formation energies of different crystal phases of NiOOH including β-NiOOH, β-Ni(OH)2 and α-Ni(OH)2 . We follow several diffusion paths and mechanisms in several phases, both across layers and through them. We pin down the reason for efficient diffusion laterally on a layer and explain why diffusion through a layer is impossible. Our results suggest that hydrogen transfer may be possible for the β-NiOOH phase with hydrogen added interstitially and transferred along the layers. This study significantly advances our understanding of diffusion in an uncommonly structured material.